Financial market and growth: Evidence from postreforms India - Prity Sinha; Brinda Viswanathan; Badri G. Narayanan (Cogent Economics & Finance, 2015)
A significant boom occurred in the Indian financial market and growth in the post-liberalization era. This motivates us to analyze the impact of stock market and credit market (two components of financial market) for the growth of financial market. This paper attempts to show the linkage between stock and credit markets and their impact on the Indian economy taking the period after post-liberalization. The period of analysis is from 1994 to 2010; we identify the three variables as stationary and find a relationship between the financial market and gross domestic product (GDP) and a long-run effect of lagged differences in credit market on GDP. It has been inferred that stock market development has larger and more significant long-run mutual effects on economic growth than credit market development in India.
Keywords: 330; finance; India; reforms; stock markets; credit markets; time-series analysis